THE USE OF SCRABBLE GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Dhea Fery Aprillandi Putra; Tatang Setia (Institut Pendidikan Indonesia Garut, 2018)
The study is entitled “The Use Of Scrabble Game In Improving Students’ Vocabulary Mastery”. The study was attempted to figure out whether the use of Scrabble game could improve the students’ vocabulary mastery. To attain these objectives, 31 students of second grader of Senior High School 6 Garut were involved. The researcher applied quantitative study in pre-experimental design. The data were obtained through the analysis of students’ pre-test, and post-testing class. The findings revealed that the students had lack of ability in vocabulary. The Score of pre-test shown that 87, 1 % with the total students of 27 didnot meet the minimun criteria and only 12, 9 % had meet the minimun criteria. But, the post-test result shown the opposite result that is The Score of post-test shown that 87, 1 % with the total students of 27 meet the minimun criteria and only 12, 9 % had meet the minimun criteria. It is also supported by the the result of paired T-Test shown Ha was accepted, because the computation of t-test on the data shows that ???????????????????????????????????? ≤ ???????????????????????????????????? ≥ ???????????????????????????????????? (2,0423 ≤ 11,0620 ≥ 2,0423 ) and it means that Ha is accepted and H0 is rejected. In other word, there is a significant influence of the use of Scrabble game and students’ vocabulary mastery. It was concluded that Scrabble game could improve students’ vocabulary mastery.